Effect of Hybrid Discrete Fibers on Mechanical Properties of FRC. (December 2018) - Wtaife, Salam; Shaban, Alaa; Alsabbagh, Ahmed; Alshammari, Emad; Suksawang, Nakin
Abstract: Combining micro and macro fibers provide high performance of fiber reinforced concrete before and after concrete matrix cracks. Concretes including different volume content of hybrid discrete fibers were evaluated regarding compressive, elastic modulus, and tensile splitting strength. Eight cases include seven types of hybrid composites that were constructed using fiber combinations of PVA and Polyolefin fibers. Test results showed that the PVA, Polyolefin, hybrid fibers reduce the compressive strength properties of concrete, especially with high volume content (2%). On the other hand, hybrid fibers improve significantly the tensile strength of concrete that leads to change the concrete behavior from brittle materials to ductile.